The low‑carbon city initiative and urban inbound tourismeconomy: a spatial difference‑in‑differences analysis - Jiafeng Gu (Environment, Development and Sustainability, 2024)
Although tourism is often treated as one of the crucial industries for the construction of low-carbon cities (LCCs), there is no systematic evidence on whether there is a causal relationship. This research aims to explore and empirically test the causal link between LCC initiatives and inbound tourism of cities using a spatial difference-in-differences approach with balanced panel data of 59 Chinese major tourism cities from 2000 to 2017. The results show that urban tourism by foreign tourists exhibits significant spatial spillover effects. Compared to non-LCCs, the number of foreign tourists on LCCs increased by 4.7 percentage points and the average length of stay of foreign tourists increased by 3.6 percentage points. The direct impact of the LCC initiative on foreign tourists was significant, while the indirect impact was insignificant. The findings of the study not only deepen the researchon sustainable tourism behavior of inbound tourists, but also provide valuable references for cities to participate in the competition in the international tourism market through low-carbon development.